Influence of serum adiponectin on baseline albuminuria and subsequent decline in eGFR in African Americans: The Jackson Heart Study - Mohit Agarwal; Prakrati C. Acharya; Aditi Kumar; Norah Sohail; Luis A. Juncos; Bessie A. Young (PLoS ONE, 2025)
Purpose Few studies to date have examined the relationship of adiponectin with kidney disease in an exclusively African American (AA) population. The purpose of this study was to determine whether serum adiponectin was an independent predictor of the presence of albuminuria or decline in estimated glomerular filtration rate (eGFR) in AA. Methods The study included 5,301 AA participants enrolled in the Jackson Heart Study (JHS), Exam 1 and 3 (2000–2013). The primary outcome measure was the decline in eGFR. Cross sectional analyses were used to assess the relationship between albuminuria and serum adiponectin. Longitudinal analyses were used to assess the relationship between eGFR decline and adiponectin. Results Nearly 2/3 of subjects were women (63.5%) and about half (52%) of the participants were middle aged (45–65 years). Mean eGFR was 94.15 (±SD 21.98) mL/min/1.73 m 2 and 6.30% of subjects had eGFR < 60 mL/min/1.73 m 2 Mean serum adiponectin levels were 5408.69 ng/mL (±SD 4,280.32 ng/mL) and women had higher serum adiponectin levels 6139.14 ng/mL (±SD 4553.57 ng/mL) than men 4148.91 ng/mL (±SD 3414.43 ng/mL) (p < 0.001). Analyses revealed positive correlation between adiponectin levels and albuminuria (P = 0.001), an association significant only in men. During a median duration of follow up of approximately 8 years, a higher baseline adiponectin was associated with a subsequent higher decline in eGFR. Due to the skewed distribution and to facilitate the interpretation of results, we transformed baseline Adiponectin values to log base 2. So a unit higher baseline Log based 2 Adiponectin indicates a level two times the lower value. And an African American man with twice the baseline value of adiponectin had a risk of 2.22 mL/min/1.73 m 2 higher subsequent decline in GFR (95% CI: −3.72 to −0.73; P = 0.003) over the study period. This effect was not seen in women. On further subgroup analysis of those with a rapid kidney function decline (eGFR rate loss >3.5 mL/min/year), the correlation between adiponectin and eGFR became more prominent (4.7 mL/min/1.73 m 2 decline in eGFR per 10 years) (P = 0.006). No association was seen between baseline adiponectin and progressive eGFR decline in subgroups of men without rapid kidney function decline. Conclusion In AA men, elevated adiponectin level at baseline is an independent predictor of albuminuria and subsequent decline in eGFR.